2021
DOI: 10.1177/23743735211056521
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, Knowledge, Attitude and Empathy Levels of Dental Postgraduates Towards Their Patients During Practice and Research—A Questionnaire Based Survey

Abstract: Empathy is vital in ensuring the quality of the patient-clinician relationship. Empathy in the health care setting is the ability to understand a patient's experiences and feelings and communicate this understanding for better clinical outcomes in dental treatments. The study aimed to compare levels of empathy in post-graduate dental students across the different years of the master's degree course. Questionnaire forms distributed among post graduate students and awareness, knowledge, attitude, and empathy lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
2
0
0
Order By: Relevance
“…Among all the factors, AT had the highest impact on EVPI. This finding is consistent with other studies in the literature [30,56,80,128,129]. Refs.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Among all the factors, AT had the highest impact on EVPI. This finding is consistent with other studies in the literature [30,56,80,128,129]. Refs.…”
Section: Discussionsupporting
confidence: 94%
“…We found that 1 unit of increase in perceived behavioral control positively affected EVPI by 0.25 units. This finding is consistent with the previous studies in the literature [30,56,66,80,96,128]. Given the correlation between consumers' PBC and EVPI, the difficulties associated with purchasing EVs rather than conventional vehicles (price comparisons, habit changes, innovative actions, psychological and functional challenges, etc.)…”
Section: Discussionsupporting
confidence: 92%